2011
DOI: 10.1111/j.1574-695x.2011.00786.x
|View full text |Cite
|
Sign up to set email alerts
|

Porphyromonas gingivalisstimulates monocyte adhesion to human umbilical vein endothelial cells

Abstract: Monocyte recruitment to the endothelium is a crucial step in the inflammatory response that precedes the development of atherosclerosis. We assessed the effect of Porphyromonas gingivalis on monocyte adhesion to endothelial cells, cytokine production during monocyte/endothelial cell co-culture, and the expression of cell adhesion molecules on human umbilical vein endothelial cells (HUVEC) and their ligands on monocytes. Porphyromonas gingivalis challenge significantly increased the adhesion of THP-1 monocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 33 publications
1
32
0
Order By: Relevance
“…In preparation for this study, we ran experiments with MOIs of 10, 100, and 1,000 (data not shown). Results of studies using various MOIs, including the MOIs of 10 (18), 100 (19,20), and 1,000 (18), have been previously reported in the literature. The optimum concentration achieved in our experiments-in line with most publications in the literature-was the MOI of 100.…”
Section: Methodsmentioning
confidence: 99%
“…In preparation for this study, we ran experiments with MOIs of 10, 100, and 1,000 (data not shown). Results of studies using various MOIs, including the MOIs of 10 (18), 100 (19,20), and 1,000 (18), have been previously reported in the literature. The optimum concentration achieved in our experiments-in line with most publications in the literature-was the MOI of 100.…”
Section: Methodsmentioning
confidence: 99%
“…Increased expression of Eselectin and production of proinflammatory cytokines in the endothelium play a pivotal role in the generation of leukocyte infiltrates and subsequent atherosclerotic plaque formation (16,28). P. gingivalis infection significantly increases endothelial expression of VCAM-1, ICAM-1, and E-selectin, enhances production of interleukin-6 (IL-6), IL-8, and monocyte chemoattractant protein 1 (MCP-1), and increases adhesion of THP-1 monocytes to endothelial cells (18,46). Therefore, P. gingivalis elicits a proatherogenic response in endothelial cells.…”
mentioning
confidence: 99%
“…The results demonstrated that biochanin A inhibited the expression of TNF-α and IL-8 in LPS-stimulated human vascular endothelial cells in a dose-dependent manner. The adhesion of neutrophils to the endothelium is a crucial step in the inflammatory response which precedes the development of atherosclerosis [12]. VCAM-1, ICAM-1 and E-selectin recruit leukocytes to the sites of inflammation [36].…”
Section: Discussionmentioning
confidence: 99%